Consideraciones de diseño para intercambiar electrónicamente recursos académicos digitales a nivel interinstitucional - Sierra-Alean, Diego Alejandro; Suárez-Murcia, Angie Carolina; Barón-Velandia, Julio (Revista Científica, 2020)
For the exchange or loan of educational resources at the inter-institutional level, both public and private entities have their own procedures and specifications, being common in all the long period of time required for the approval of a loan and the need to move to said institution to perform the query according to the availability of defined time. The objective of this paper is to present a software design that allows the transaction of academic resources between two educational entities, in order to reduce time in the execution of the process. The implementation of the model is based on the proposed stages of the Scientific Method and the Unified Process, applying electronic negotiation specifications defined in ebXML, to define, through agreements and profiles, conditions of use of the requested resource. By implementing the software model, the execution times of the business process from several months to a couple of minutes are shortened when all the exchange is carried out by electronic means, in addition to communication without geographical limitations, favoring both students and entities for the exchange of intellectual property remotely.